An improved solvent-free system for the microwave-assisted decarboxylation of malonate derivatives based on the use of imidazole. Issue 43 (28th October 2015) - Tellitu, Imanol; Beitia, Itziar; Díaz, Marta; Alonso, Argiñe; Moreno, Isabel; Domínguez, Esther
Abstract: A comparative study of the thermal and microwave-assisted decarboxylation of a series of mono- and disubstituted monohydrolyzed malonate derivatives has been carried out. It has been found out that in both circumstances the use of imidazole has a profound effect on the success of the reaction. In general terms the assistance of microwave irradiation accelerates the decarboxylation process significantly and, at the same time, permits the use of minored temperatures with respect to the thermal via. It has been also found that both the thermal and the microwave-assisted transformation can be developed under solvent-free conditions. Graphical abstract: